2010
DOI: 10.1155/2011/198042
|View full text |Cite
|
Sign up to set email alerts
|

A Missense Mutation in Canine CLN6 in an Australian Shepherd with Neuronal Ceroid Lipofuscinosis

Abstract: The childhood neuronal ceroid lipofuscinoses (NCLs) are inherited neurodegenerative diseases that are progressive and ultimately fatal. An Australian Shepherd that exhibited a progressive neurological disorder with signs similar to human NCL was evaluated. The cerebral cortex, cerebellum, and retina were found to contain massive accumulations of autofluorescent inclusions characteristic of the NCLs. Nucleotide sequence analysis of DNA from the affected dog identified a T to C variant (c.829T>C) in exon 7 of CL… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
51
0
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(56 citation statements)
references
References 16 publications
(27 reference statements)
4
51
0
1
Order By: Relevance
“…y The primarily green autofluorescence of the lipopigment in the present 3 cats was consistent with previous reports of NCL in cats, a ferret, and a Vietnamese potbelly pig, 4,6,21,23 but the storage material in most dogs with NCL tends to exhibit bright yellow autofluorescence at similar excitation wavelengths. 7,13,14,28 Interspecies diversity of the lipopigment constituents and/or differences in the fluorescence microscopy equipment and/or protocol may explain this apparent disparity. The typical distribution of CNS lesions observed in NCL correlates well with the pathological presentations of the present 3 cases.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…y The primarily green autofluorescence of the lipopigment in the present 3 cats was consistent with previous reports of NCL in cats, a ferret, and a Vietnamese potbelly pig, 4,6,21,23 but the storage material in most dogs with NCL tends to exhibit bright yellow autofluorescence at similar excitation wavelengths. 7,13,14,28 Interspecies diversity of the lipopigment constituents and/or differences in the fluorescence microscopy equipment and/or protocol may explain this apparent disparity. The typical distribution of CNS lesions observed in NCL correlates well with the pathological presentations of the present 3 cases.…”
Section: Discussionmentioning
confidence: 99%
“…26 In dogs, the detection of causative NCL candidate genes has been restricted to purebreds, including American Staffordshire Terriers (ARSG), 1 American Bulldogs (CTSD), 2 Tibetan Terriers (ATP13A2), 7 Dachshunds (TPP1 and PPT1), 13,28 an Australian Shepherd (CLN6), 14 English Setters (CLN8), 15 and Border Collies (CLN5). 19 Similarly, purebred sheep such as Borderdales (CLN5), 8 South Hampshires (CLN6), 25 and White Swedish Landraces (CTSD) 29 comprise the majority of reports of ovine NCL.…”
mentioning
confidence: 99%
“…Among the animal species, NCLs have most frequently been reported in dogs. Previous studies have identified 9 different mutations in the canine orthologs of 8 of the 13 genes associated with human NCL as shown in Table 1 [10][11][12][13][14][15][16][17][18][19][20][21][22]. Prior to the discovery of the causative mutations, NCL was common in three dog breeds: the Tibetan Terrier, the Border Collie, and the American Bulldog [23][24][25][26].…”
Section: Introductionmentioning
confidence: 99%
“…The identification of the mutations responsible for the NCL in each of these breeds [12,[17][18][19] has led to the development of DNA tests that revealed the identity of asymptomatic heterozygous mutation carriers and, thereby, has assisted dog breeders in their efforts to reduce the incidence of NCL in these breeds [24,25]. The NCLs in most of the other dog breeds appear to be rare [10,11,[13][14][15][16]. DNA-based screening to identify mutation carriers would not be cost-effective in these breeds except in breeding lines where dogs with the disease have already been identified.…”
Section: Introductionmentioning
confidence: 99%
“…Concernant les maladies à composantes génétiques « simples » ou supposées simples, de nombreux travaux font actuellement état de l'identification de gènes responsables d'affections partagées entre l'homme et le chien, comme, par exemple, des rétinopa-thies (Wilk et al 2008), la sclérose amyothrophique latérale (Awano et al 2009), des maladies cardiaques (Meurs et al 2010), les lipofuscinoses neuronales canines (Abitbol et al 2010 ;Katz et al 2011), les épilepsies (Lohi et al 2005 ;Sepalla et al 2011), des maladies dermatologiques telle que l'ichtyose (Grall et al 2012), ou encore des anomalies comme le phénotype sans poil des chiens nus (Drogemuller et al, 2008).…”
Section: Identification Des Bases Génétiques De Maladies D'intérêt Chunclassified